Complexity and informational privacy: A study in the systemic perspective - De Moraes, João Antonio [UNESP]; Gonzalez, Maria Eunice Quilici [UNESP] (Taylor & Francis, 2018)
From the perspective of complex systems theory, the problem of informational privacy can be formulated as follows: How can privacy be analyzed in light of the insertion of information technologies into everyday life? The interaction of individuals with information technology has provided new possibilities for action, which make it difficult to identify the boundaries between public and private. The adoption of the systemic perspective in the analysis of informational privacy provides an appropriate investigation method for philosophical-interdisciplinary reflection on new themes in the contemporary scenario of digital technologies. In this chapter, the authors evaluate the problem of privacy and consider it in the light of other factors that have contributed to the complexity of human life in the contemporary world.